Metode Pembelajaran Piano untuk Remaja Autis di Modern Kawai Music School - Trifena Ruth Clara; Astri Chintya Astana (Journal on Education, 2024)
This research aims to obtain accurate data regarding the piano learning process for autistic teenagers at Modern Kawai Music School, focusing on objectives, methods, materials, media and evaluations. The study adopts a qualitative approach with a case study method, using data collection techniques such as observation, interviews, literature review and documentation. The collected data is analyzed through interview transcripts, data reduction and data presentation. The research findings drom gathered data indicate tha objectives sought are to strengthen the existing abilities, with the hope that students can grow and develop better in terms of motor skills, emotions, concertation, attitude, behavior and self regulation. The methods used in this study include lectures, demonstrations and drills. The materials employed aligh with the general piano curriculum. The evaluation process for piano learning among autistic teenagers at Modern Kawai Music School involves annual examinations and regular assessments during class sessions. Some students have been able to follow the general curriculum due to their improved skills and behaviors. Consequently, it can be concluded that the piano learning program for autistic teenagers at Modern Kawan Music School is effective, as it has successfully achived its objectives.